HIV-related-post-traumatic stress disorder : psychological distress among a sample of individuals recently diagnosed with HIV - Martin, Lindi Imelda (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2008.